ANALISIS PERBEDAAN GAYA HIDUP DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA MEREK ADIDAS DI SURABAYA - PUSPITA, YOHANA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:The growth ofthe shoesindustriesin Indonesiacreatea highly competitivecompetitionfortheshoes manufacturersin Indonesia. Similarly,the market shareof foreignbrands ofsport shoeswere alsoincreased rapidly, one of whichis theAdidasbrandsports shoes. Consumers were interested inbuyingandusing theAdidasbrand sportsshoesbecauseone of themis affectedbylifestyle. Where, lifestyledimensionsthat influenceconsumerspsychographicofteninterpretedas a measure ofAIO(activity, interest, opinion)the measurement ofactivities, interests, andopinionsof consumers. Lifestyle indicator are entertainment, sports, media, fashion, and opinion.Population in this study are men and women aged 20-40 years who have purchased at least two times and use brand Adidas sports shoes. The sample using judgment sampling technique with the sample size of 110.Measuring instrument is used a questionnaire, and the data is analyzed by cluster. Keywords: lifestyle, purchase decision, cluster.